RUBBER CONSUMPTION MARKETS IN KELURAHAN AIR TIRIS, KAMPAR DISTRICT, KAMPAR DISTRICT 2016 - Ellyana "; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is entitled Market for Rubber Farmers Consumption in Air Tiris Village, Kampar District, Kampar Regency in 2016. This research is a descriptive research with a qualitative approach. The location of the study was conducted in the Air Tiris Sub-District of Kampar District, Kampar Regency, as for the reason for choosing a location because Kampar Subdistrict was a very potential area in the plantation sector and there were still many problems encountered, especially the problem of infrastructure and plantation quality. Informants in this study were employees of the Plantation Office and rubber farm workers. The informants were determined by researchers, namely as many as 4 rubber farmers who were core informants, 1 employee of the Plantation Office and 1 employee of the Central Statistics Agency.The results obtained in this study are 1) Food needs of rubber farmers in the Air Tiris Village of Kampar District, Kampar Regency in 2016, namely rice, major vegetables, fish and various animal proteins. For non-educational consumption, transportation, information and communication. 2) Usually rubber farmers work laborers on other people's land / join construction work, also plant sweet potatoes and rice in the fields. 3) The Kampar District government program in the procurement of food and non-food needs in the Air Tiris Sub-District of Kampar District in Kampar Regency in 2016. The Department of Plantation Livestock and Animal Health (Disbunnak Keswan) formed the Kampar Regency Joint Business Group (KUB). In addition, the sub-dept. And disperindag also carried out increasing individual capacity, involving several roles / tasks of consultation, supervision, monitoring and evaluation.Keywords: Consumption Market, Rubber Farmers